2017
DOI: 10.1097/mpa.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Expression Profiling for Gemcitabine-Related Genes (hENT1, dCK, RRM1, RRM2) in Patients With Resectable Pancreatic Adenocarcinoma Receiving Adjuvant Chemotherapy

Abstract: Expression of hENT, RRM1, and dCK genes provides important prognostic information for PDAC patients treated with adjuvant gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
2
28
2
Order By: Relevance
“…Currently the functional significance of PKMYT1 in prostate cancer remains unclear, and it makes sense to determine whether PKYMT1 is indispensable in prostate cancer, which requires further investigation. The ribonucleotide reductase M2 subunit (RRM2) plays important role in several human cancers, including colorectal cancer, hepatocellular carcinoma, pancreatic adenocarcinoma, and breast cancer (Lee et al, 2014;Sierzega et al, 2017;Nana et al, 2018;Chen et al, 2019). Increased expression of RRM2 has been demonstrated to be a mechanism driving poor patient outcomes in prostate cancer, in accordance with our findings (Mazzu et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Currently the functional significance of PKMYT1 in prostate cancer remains unclear, and it makes sense to determine whether PKYMT1 is indispensable in prostate cancer, which requires further investigation. The ribonucleotide reductase M2 subunit (RRM2) plays important role in several human cancers, including colorectal cancer, hepatocellular carcinoma, pancreatic adenocarcinoma, and breast cancer (Lee et al, 2014;Sierzega et al, 2017;Nana et al, 2018;Chen et al, 2019). Increased expression of RRM2 has been demonstrated to be a mechanism driving poor patient outcomes in prostate cancer, in accordance with our findings (Mazzu et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Some reports have indicated that when GEM was administered iv, the hENT1 expression level correlated with the anticancer effects of GEM, such as overall survival and disease‐free survival (Maréchal et al, , ; Nakagawa et al, ; Sierzega et al, ), whereas our results indicated that hENT2 would have a more important role in GEM uptake by metastatic tumor in GEM‐HAI therapy. This discrepancy is probably due to the difference in the administration route of GEM, because the topical concentration of GEM in metastatic tumor is much higher in GEM‐HAI therapy than in iv administration.…”
Section: Discussioncontrasting
confidence: 44%
“…The precise reasons for these differences are unclear, though it is known that the expression and activity of metabolic enzymes and transporters are different among different cell types, such as normal and cancer cells or cells from different tissues. Clinical studies have also found individual differences in the expression levels of transporters, such as hENT1, hENT2, and hCNT3, and metabolic enzymes, such as ribonucleotide reductase M1 and deoxycytidine kinase (Sierzega, Pach, Kulig, Legutko, & Kulig, ). Since the origin of the pancreatic cancer cells used in this study was different (MIA‐PaCa2 cells were primary tumor cells and As‐PC1 cells were metastatic tumor cells of pancreatic adenocarcinoma), the disparity probably resulted from the different cell types (Pennycooke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…8,9) The lack of equilibrative nucleoside transporter 1 (ENT1) and deoxycytidine kinase (dCK) and increase in the levels of ribonucleotide reductase subunits M1 (RRM1) and M2 (RRM2) are involved in the development of gemcitabine resistance. [10][11][12][13] Furthermore, a clinical study reported that the expression of these four key genes influences the prognosis of patients with pancreatic cancer undergoing adjuvant chemotherapies. 14) ENT1 is a cellular transporter involved in the intracellular incorporation of gemcitabine.…”
Section: Discussionmentioning
confidence: 99%